2015
DOI: 10.1051/matecconf/20152601003
|View full text |Cite
|
Sign up to set email alerts
|

Study of Interaction between Fly Ash-cement and Bentonite Matrices

Abstract: Among the important factors characterizing the quality of sealing mixtures is strength, durability, compatibility and permeability. Experimental work was therefore conducted to assess the use of cement, fly ash, gravel and bentonite in the form of artificial self-hardening sealing mixture. The results of the work show a good compatibility between the bentonite and cement during its fly ash replacement. Compactness of the structure was confirmed by studying of permeability and SEM microscopy, which in the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…PPF can also improve the abrasion resistance of GPC mixtures by bridging cracks and preventing their propagation. Similar findings were reported by Grdic et al [73] where abrasion resistance of polypropylene fiber-reinforced concrete was evaluated. It was reported that the addition of PPF has a positive effect and aids in increasing the resistance of concrete to abrasive erosion.…”
Section: Abrasion Resistancesupporting
confidence: 88%
See 1 more Smart Citation
“…PPF can also improve the abrasion resistance of GPC mixtures by bridging cracks and preventing their propagation. Similar findings were reported by Grdic et al [73] where abrasion resistance of polypropylene fiber-reinforced concrete was evaluated. It was reported that the addition of PPF has a positive effect and aids in increasing the resistance of concrete to abrasive erosion.…”
Section: Abrasion Resistancesupporting
confidence: 88%
“…Additionally, the pozzolanic reactivity of bentonite may lead to the development of calciumsilicate-hydrate (C-S-H) gel in conjunction with geopolymer gel, which can provide an even denser microstructure of the GPC [72]. It was reported by different studies [33,72,73] that the addition of bentonite to cementitious matrices results in the development of C-S-H phases. It is also reported that CASH phases are developed when bentonite is added to fly ash-based cementitious products.…”
Section: Water Absorptionmentioning
confidence: 99%
“…Due to the finer particle size of bentonite than the fly ash, it can have a uniform distribution in the mix matrix of both the GNAC and GRAC, thus providing a more compact and denser microstructure. In addition, the pozzolanic reactivity of bentonite may have resulted in the development of C-S-H gel in combination with geopolymeric gel that can provide a further denser microstructure of geopolymer matrix [65,66]. Therefore, it can be inferred that the incorporation of bentonite in both the GNAC and GRAC mixes is beneficial in terms of reducing the water absorption capabilities of the geopolymer matrix.…”
Section: Water Absorptionmentioning
confidence: 99%